An Exploratory Study of Borderline and Narcissistic Personality Disorder among Alcohol Consumers - Khadka, Chetan (The Journal of Knowledge and Innovation, 2023)
The rising prevalence of alcoholism has prompted numerous studies investigating its co- occurrence with mental health disorders. This research investigates the connection between alcohol dependency and the co-occurrence of borderline personality disorder (BPD) and narcissistic personality disorder (NPD) traits in individuals residing in Biratnagar. It aims to assess the prevalence of BPD and NPD symptoms in alcohol consumers using an exploratory quantitative research design. The sample consisted of 100 respondents from ward number 12 of Biratnagar Metropolitan City. BPD is associated with an addictive personality, extending beyond substances, while NPD involves distorted perceptions of one’s life and others; opinions. Non-probability sampling methods were used due to the absence of official records on alcoholics in the city. Findings suggest a low likelihood of developing BPD in individuals with alcohol dependency, and alcohol consumption does not significantly contribute to the development of NPD. This research offers valuable insights into the correlation between alcohol consumption and personality disorders, shedding light on potential directions for future studies and potential clinical strategies. The research provides a foundation for improved clinical practices, future research directions, and community-based efforts to address alcohol dependency and its connection to personality disorders in Biratnagar. It underscores the need for a holistic approach to mental health and substance abuse, recognizing the complexities of individual experiences and needs